High-Efficiency Diphenylpyrimidine Derivatives Blue Thermally Activated Delayed Fluorescence Organic Light-Emitting Diodes - Sohn, Sunyoung; Ha, Min Woo; Park, Jiyong; Kim, Yoo-Heon; Ahn, Hyungju; Jung, Sungjune; Kwon, Soon-Ki; Kim, Yun-Hi (Frontiers in Chemistry, 2020)
Organic light emitting diodes (OLEDs) with Tthermally activated delayed fluorescence (TADF) emitting dopantsemitter has been developed with highly twisted donor–acceptor configurations and efficient color-pure blue emitters. In this study, Synthesized 4-(4-(4,6-diphenylpyrimidin-2-yl)phenyl)-10H-spiro[acridine-9,9'-fluorene] (4,6–PhPMAF) doped device two types of substance nitrogenous position in dipyridylpyrimidine are synthesized for color-pure and high-efficiency TADF OLEDs. Synthesized emitters with spiroacridine as a donor unit and diphenylpyrimidine as acceptor exhibit different the device characteristics that such as the luminescence, external quantum efficiencies, current efficiencies, and power efficiencies display corresponding to 213 cd/m2, 2.95%, 3.27 cd/A, and 2.94 lm/W with Commission International de l’Eclairage (CIE) CIE coordinates of (0.15, 0.11) in 4,6–-PhPMAF-doped DPEPO emitter, while. T thehe reported 10-(4-(2,6-diphenylpyrimidin-4-yl)phenyl)-10H-spiro[acridine-9,9'-fluorene] (2,6–PhPMAF) 2,4-PhPMAF-doped DPEPO emitterdevice exhibit high device performance with 1445 cd/m2, 12.38%, 19.6 cd/A, and 15.4 lm/W, which might be originated from increased internal quantum efficiency by up-converted triplet excitons to the singlet state with relatively smaller ΔEST of 0.17 eV and higher reverse intersystem crossing rate (kRISC) of 1.0×108/s in 2,6–PhPMAF than 0.27 eV and 3.9×107/s in 4,6–PhPMAF. with CIE coordinates of (0.16, 0.19). Although Despite low performance of 4,6–-PhPMAF doped device, synthesized 4,6–PhPMAF has better color-purity as a deep-blue emission with y-axis (0.11) than reported 2,6–PhPMAF with y-axis (0.19) in CIE coordinate. with CIE coordinates of (0.16, 0.19).The synthesized 4,6–PhPMAF has higher good thermal stability of any transition up to 300 oC and decomposition temperature with only 5% weight loss in 400 oC than reported 2,6-PhPMAF, it has lower device properties than the 2,4-PhPMAF-doped device. These results could be originated from improved internal quantum efficiency by up-converted triplet excitons to the singlet state with relatively smaller charge-transfer gap of ΔEST = 0.1023 eV in 2,4-PhPMAF than ΔEST = 0.282eV in 4,6-PhPMAF. The synthesized acridine and dipyridylpyrimidine-based emitters can be used for high-performance deep-blue emitters in a TADF-OLEDs.The maximum PL emission of 4,6–PhPMAF in various solvents appeared at 438 nm, which has blue-shift about 20 nm than that of 2,6–PhPMAF, which contributes deep-blue emission in synthesized 4,6–PhPMAF.